DECLINING US STATUS AS A SUPERPOWER: IMPLICATIONS FOR THE WORLD ORDER (Margalla Papers, 2021)
Since 1945, the US has been relishing the status of a superpower by following its interests through a no of means, including international order, global and regional security arrangements, and international organizations. Recently, emerging global powers have challenged the existing international order, whereas the US is on a declining trajectory. The US hegemonic obligations to use its preponderant power in global issues with the intent to cast events in its favour have brought an inevitable overstretch beyond its capacity. Furthermore. a visible shift in power centres, the backlash of political decisions, and economic recession are other factors that need to be studied. This paper, therefore, explores the highly debated and contested reasons for the US decline. While employing deductive reasoning through qualitative analysis, it evaluates the efficacy of existing international order, emerging multilateralism, and difficulties in obviating the attendant risks to US security and prosperity. Implications of a declining superpower and suggested course of action for Pakistan have also been discussed in this paper. Bibliography Entry Abbas, Muhammad, and Hassan Jalil Shah. 2021. “Declining US Status as a Superpower: Implications for the World Order.” Magalla Papers 25 (1): 131-142.